The Impact of the International Community on the State Policy of Georgia - Putkaradze, Inga (Politics / პოლიტიკა, 2021)
The aim of this paper is to determine the impact of the international community on the state policy of Georgia and the extent to which the recommendations of international institutions are reflected in the decisions taken by the government, as well as in the implementation of relevant laws and reforms. For the purposes of the research, the article examines and analyzes the electoral, constitutional and judicial reforms carried out by the Georgian authorities, “United National Movement” and “Georgian Dream” since on the basis of a case studies. The paper uses a qualitative method, which includes: analysis of secondary sources and literature, study and analysis of documents. The result of the research includes a case study, where over  the yars specific cases are discussed by the authorities from the point of view of constitutional, judicial and electoral reforms. It also compares the policies of both authorities with regard to whether they have complied with the recommendations of the international community, which includes examining the response of the international community to this issue. At the end the article, the main conclusions and results of the study are presented and summarized, as well as the corresponding answers to the hypotheses of study are given.
Keywords: International Community, International Institution, Court, Elections, Constitution, Government, Legitimacy, Democratic Conditionality, Power.